Traffic Light Control System Using 434 Mhz Radio Frequency - Ahya Ilmudin, Mohamad Hakim; Hashim, Nik Mohd Zarifie; Ja'afar, Abd Shukur; Salleh, Azahari; Jaafar, Anuar; Mohd Sam, Mohd Fazli (IJRAT, 2014)
-